Glypican-1 drives unconventional secretion of fibroblast growth factor 2 - Sparn, Carola; Dimou, Eleni; Meyer, Annalena; Saleppico, Roberto; Wegehingel, Sabine; Gerstner, Matthias; Klaus, Severina; Ewers, Helge; Nickel, Walter (eLife, 2022)
Fibroblast growth factor 2 (FGF2) is a tumor cell survival factor that is transported into the extracellular space by an unconventional secretory mechanism. Cell surface heparan sulfate proteoglycans are known to play an essential role in this process. Unexpectedly, we found that among the diverse subclasses consisting of syndecans, perlecans, glypicans, and others, Glypican-1 (GPC1) is the principle and rate-limiting factor that drives unconventional secretion of FGF2. By contrast, we demonstrate GPC1 to be dispensable for FGF2 signaling into cells. We provide first insights into the structural basis for GPC1-dependent FGF2 secretion, identifying disaccharides with N-linked sulfate groups to be enriched in the heparan sulfate chains of GPC1 to which FGF2 binds with high affinity. Our findings have broad implications for the role of GPC1 as a key molecule in tumor progression.